Plasma Lipidomics Profiling Reveals Biomarkers for Papillary Thyroid Cancer Diagnosis - Jiang, Nan; Zhang, Zhenya; Chen, Xianyang; Zhang, Guofen; Wang, Ying; Pan, Lijie; Yan, Chengping; Yang, Guoshan; Zhao, Li; Han, Jiarui; Xue, Teng (Frontiers in Cell and Developmental Biology, 2021)
The objective of this study was to identify potential biomarkers and possible metabolic pathways of malignant and benign thyroid nodules through lipidomics study. A total of 47 Papillary thyroid carcinomas（PTC） and 33 control check (CK) were enrolled. Plasma samples were collected for UPLC-Q-TOF MS system detection, and then OPLS-DA model was used to identify differential metabolites. Based on classical statistical methods and machine learing, potential biomarkers were characterized and related metabolic pathways were identified. According to the metabolic spectrum, 13 metabolites were identified between PTC group and CK group, and A total of 5 metabolites were obtained after further screening. Its metabolic pathways were involved in glycerophospholipid metabolism, linoleic acid metabolism, alpha - linolenic acid metabolism, glycosylphosphatidylinositol (GPI) - anchor biosynthesis, Phosphatidylinositol signaling system and the metabolism of arachidonic acid metabolism.The metabolomics method based on PROTON nuclear magnetic resonance had great potential for distinguishing normal subjects from PTC. GlcCer(d14:1/24:1), PE-NME (18:1/18:1), SM(d16:1/24:1), SM(d18:1/15:0) and SM(d18:1/16:1) can be used as potential serum markers for the diagnosis of PTC.